STRATEGI MENGATASI MADRASAH MISKIN MELALUI PENGEMBANGAN MODEL MANAJEMEN BERBASIS KOLABORASI (PENELITIAN TINDAKAN KEPENDIDIKAN DI BERBAGAI JENJANG MADRASAH DI PROVINSI BENGKULU) - Rambat Nur Sasongko (Jurnal Madania)
The Strategy in Improving Under Developed Islamic School through Developing Collaboration Based Management (a Study of Educational Action research in Any Levels of Islamic School in Bengkulu). This research is aimed at developing the model of collaboration based Islamic school (madrasah) management in order to solve many problems in poor madrasah. The study absolutely used educational action research method. The subject of this study consists of head masters, teachers, administration staffs, parents, and others stakeholders in several Islamic schools in Bengkulu. The data were collected by using questionnaire, interview, observation, and documentation. The collected data analyzed were used by quantitative and qualitative technique. The result of this study shows that the developing model of collaboration based Islamic school management can increase fully equipped national standard of education in poor Islamic school. The model of collaboration based Islamic school management needs optimal head master role, timing flexibility, solid teamwork, and community role. Such model is capable of solving many problems owned by poor Islamic school in Bengkulu